Risk Factors for Seropositivity to Kaposi Sarcoma–Associated Herpesvirus Among Children in Uganda - Wakeham, Katie; Webb, Emily L.; Sebina, Ismail; Nalwoga, Angela; Muhangi, Lawrence; Miley, Wendell; Johnston, W. Thomas; Ndibazza, Juliet; Whitby, Denise; Newton, Robert; Elliott, Alison M. (Journal of acquired immune deficiency syndromes, 2013)
Determinants of Kaposi sarcoma–associated herpesvirus (KSHV) seropositivity among children living in sub-Saharan African populations where infection is endemic are not well understood. Local environmental factors, including other infectious agents, may be key. Within the context of a well-characterized birth cohort, we examined associations between various factors and antibodies against KSHV, measured in stored plasma samples from 1823 mother–child pairs in Entebbe, Uganda.
Keywords: Kaposi sarcoma-associated herpesvirus; Sub-Saharan Africa; Children; HIV; Kaposi sarcoma